CUSTOMER CHARACTER ANALYSIS OF CATERING SERVICESFOR CELEBRATION NEEDS IN SIDOARJO - Preiselia Constella Yudita Putri; Amin Sadiqin (Nindikayla Institute, 2023)
This study aims to assess the behavior of customers who use catering services in Sidoarjo. The type of research used is a description experiment using several variations in the behavior of resource persons. This study used frequency tables, bar charts, and cross-tabulations data processing methods. The process of obtaining resource persons in this study uses convenience samples. This research was obtained from experiments based on the type of healthn male and female speakers. Based on the dissemination of the frequency of age and work of the interviewees. Some kinds of catering services that are often used are buffets with the most principle is efficient. The side that encourages the resource persons is friends and resource persons who use the speaker's services during the celebration. The catering used by the resource person is CV CATHLEA CATERING, the resource person obtained catering information throughfriends. The most resource persons use catering services every year and feel satisfied using catering services. Most of the speakers were satisfied because they were by customers' wishes